2016
DOI: 10.1002/lary.25932
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary experiences in trachea scaffold tissue engineering with segmental organ decellularization

Abstract: NA Laryngoscope, 126:2520-2527, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 37 publications
2
57
0
Order By: Relevance
“…Taking oxygen and expelling carbon dioxide is a function of the respiratory system, which is formed by multiple organs. Some of them, such as the trachea, lungs, and even diaphragm, have been tested as raw materials for decellularization purposes [133][134][135].…”
Section: Tissues Related To Respiratory Systemmentioning
confidence: 99%
“…Taking oxygen and expelling carbon dioxide is a function of the respiratory system, which is formed by multiple organs. Some of them, such as the trachea, lungs, and even diaphragm, have been tested as raw materials for decellularization purposes [133][134][135].…”
Section: Tissues Related To Respiratory Systemmentioning
confidence: 99%
“…A recent study of IBTA showed that an autologous patch grown using IBTA could serve as resorbable, constructive scaffold for the repair of partial circumference trachea in a rabbit model. 8 Regeneration of epithelium and chondrocytes was confirmed. In the present study, we examined the usefulness of BIOTUBE for the circumferential tracheal replacement.…”
Section: Discussionmentioning
confidence: 87%
“…7 The postmortem examination of the transplanted segment showed a grossly significant collapse of the tracheal tubular structure. 8 The in-body tissue architecture (IBTA), based on an encapsulation reaction, can produce autologous implantable tissue. Nakayama and colleagues reported the successful implantation of small diameter vascular grafts, "BIOTUBEs" produced by IBTA technology.…”
Section: Introductionmentioning
confidence: 99%
“…The updates in creating tracheal grafts have been demonstrated through protocol improvements in physical decellularization, chemical decellularization, and bioreactor methods in the past five years. [73][74][75][76][77] These protocol advancements have also been seen in other organ systems using animal-based models such as esophagus (murine-rat), 78 lung (ovine), 79 cartilage (porcine), 80 uterus (ovine and leporine), 81,82 bladder (leporine), 83 pericardium (bovine), 84 submillimeter vasculature (murine-rat), 85 and intestine (murine-mouse) 86 model tissues. Protocol advancement in the field of vasculature has been especially important given this is often viewed as a challenge due to the size and difficulty of reseeding these grafts with endothelial cells.…”
Section: History and Development Of Decellularization For Bioenginementioning
confidence: 85%